THE PROBLEM OF DOPING IN GLOBAL SPORTS AND STRATEGIES FOR ITS PREVENTION - Ergasheva Muxlisa G‘ulomjon qizi (Ustozlar uchun, 2025)
Annotation: This article examines the problem of doping in global sports, its negative impact on athletes and the sports system, international legislation and monitoring mechanisms, as well as effective strategies for combating doping. The study discusses ways to create a clean sports environment, strengthen the principles of fair competition, and highlights the role of international sports organizations in promoting doping-free sports.